Workshop Penulisan Proposal dan Laporan Karya Ilmiah untuk Dosen dan Mahasiswa - Revi Lestari Pasaribu; Asep Nursangaji; Ade Mirza; Yulis Jamiah; Silvia Sayu (LPPM UNINUS, 2022)
This PKM activity started from the interest of lecturers at the Mathematics Education Study Program at Tanjungpura University to write proposals and reports for lecturers and students in West Kalimantan following the regulations of the Ministry. The form of this PKM is a workshop with the title